Systematic Characterization of Long Noncoding RNAs Reveals the Contrasting Coordination of Cis- and Trans-Molecular Regulation in Human Fetal and Adult Hearts. (April 2016) - He, Chunjiang; Hu, Hanyang; Wilson, Kitchener D.; Wu, Haodi; Feng, Jing; Xia, Siyu; Churko, Jared; Qu, Kun; Chang, Howard Y.; Wu, Joseph C.
Abstract : Background—: The molecular regulation of heart development is regulated by cis - and trans -factors acting on the genome and epigenome. As a class of important regulatory RNAs, the role of long noncoding RNAs (lncRNAs) in human heart development is still poorly understood. Furthermore, factors that interact with lncRNAs in this process are not well characterized. Methods and Results—: Using RNA sequencing, we systematically define the contrasting lncRNA expression patterns between fetal and adult hearts. We report that lncRNAs upregulated in adult versus fetal heart have different sequence features and distributions. For example, the adult heart expresses more sense lncRNAs compared with fetal heart. We also report the coexpression of lncRNAs and neighboring coding genes that have important functions in heart development. Importantly, the regulation of lncRNA expression during fetal to adult heart development seems to be due, in part, to the coordination of specific developmental epigenetic modifications, such as H3K4me1 and H3k4me3. The expression of promoter-associated lncRNAs in adult and fetal hearts also seems to be related to these epigenetic states. Finally, transcription factor–binding analysis suggests that lncRNAs are directly regulating cardiac gene expression during development. Conclusions—: We provide a systematic analysis of lncRNA control of heart development that gives clues to the roles that specific lncRNAs play in fetal and adult hearts. Abstract : Supplemental Digital Content is available in the text.